Hypomania Induced by Subthalamic Nucleus Stimulation in a Parkinson’s Disease Patient: Does It Suggest a Dysfunction of the Limbic Circuit? - Ji Seon Kim; Hee Jin Kim; Ji-Young Lee; Jong Min Kim; Ji Young Yun; Beom S. Jeon (Journal of Movement Disorders, 2012)
The aim of this report was to describe a case of hypomania after deep brain stimulation of the subthalamic nucleus (STN DBS) in a Parkinson’s disease (PD) patient. 59-year-old man with a 15-year history of PD underwent bilateral implantation of electrodes to the STN. Immediately after surgery, his motor function was markedly improved and his mood was elevated to hypomania. Fusion images of the preoperative MRI and postoperative CT scan showed that the electrodes were located in the medial portion of the STN. In this case, behavioral mood change was related to the deep brain stimulation. Moreover, the anatomical location and the functional alteration of the STN after the DBS surgery might be related to the regulatory system of the associative and limbic cortico-subcortical circuits.